Sensitivity of blood cells maturation pattern in the diagnosis of Myelodysplastic Syndrome using flow cytometry - a systematic review - Sinin Nur Jihan, Abd Hamid Nazefah, Zulkifli Noor Fadzilah, Othman Ainoon, Mustafa Halimah, Ahmad Asnawi Asral Wirda, (Universiti Pendidikan Sultan Idris, 2016)
Sensitivity of blood cells maturation pattern in the diagnosis of Myelodysplastic Syndrome using flow cytometry - a systematic review by Sinin Nur Jihan, Abd Hamid Nazefah, Zulkifli Noor Fadzilah, Othman Ainoon, Mustafa Halimah, Ahmad Asnawi Asral Wirda,